PANDANGAN ISLAM TENTANG PILIHAN KEHIDUPAN WANITA KARIR PADA ERA 4.0 REFOLUSI INDUSTRI - Susanti, Liana Dewi (Center of Gender Studies and Child of State Islamic Institute of Metro, 2019)
Islam came as a religion that Rahmatan Lil ‘Aalamiin taught to enjoy the world and what is inside. With the condition that it remains within the limits set by Allah SWT. Islam even requires humans to take advantage of all the good that is provided by God because all that sustains welfare. Islam also does not forbid women of a career but requires that women remain obedient to their gods and messengers and do righteous deeds. The Industrial Revolution 4.0 caused a rapid transformation of social life. Digitalisation of technology cannot be dammed and continues to affect various fields of life. Women must be able to adapt to these conditions, overcome challenges, and take opportunities to play a role in the 4.0 Industrial Revolution. President Jokowi and government officials have responded and anticipated this development through policies and budget allocations. HR development was a major factor in achieving the success of the Industrial Revolution 4.0. However, regulations are also needed to support progress while protecting the community. One of them can be through the revision of Law Number 19 Year 2016 concerning Information and Electronic Transactions (UU ITE). In amending the Law various issues related to the Industrial Revolution 4.0 also need to regulate the principle of gender equality and the involvement of women in it.